Profesional Skeptimisme Auditor dan Kualitas Audit dalam Era Blockchain (Auditor Professional Skepticism and Audit Quality in The Blockchain Era) - Wijaya, I Nyoman Agus; Setiana, Sinta; Rusyana, Finna (Akutansi Bisnis & Manajemen ( ABM ), 2023)
This research aims to identify the influence of professional skepticism on audit quality through blockchain technology as a moderating variable. This research also tries to find determining factors that can increase auditors' professional skepticism. Data analysis was carried out using SEM-PLS, with auditor analysis units in Indonesia. Data was collected through questionnaires sent to auditor managers, senior auditors and junior auditors as objects receiving pressure from clients in insurance engagements. The research results show that auditors' professional skepticism has a positive influence on audit quality. The interaction between client time limit pressure and audit quality is strengthened by the presence of professional skepticism. These findings conclude that auditors must increase professional skepticism in technological sophistication to improve audit quality. In addition, the results of this study indicate that the pressure of client time constraints has a positive influence on professional skepticism.